Increasing Tolerance Awareness Through Active Learning at SMAN 1 Pancung Soal - Usman Efendi (BiCED Proceeding, 2024)
This study aims to explore the impact of active learning on increasing students' awareness of tolerance at SMAN 1 Pancung Soal. The research was conducted using a Classroom Action Research (CAR) approach, involving two cycles of intervention. The first cycle showed improvements in student interaction and understanding of tolerance values, but challenges such as unequal participation and hidden stereotypes remained. The second cycle resulted in significant progress, with 90% of students actively engaging in the activities, demonstrating improved collaboration and a deeper understanding of tolerance. The findings suggest that active learning is an effective approach to fostering tolerance in a diverse classroom, although ongoing attention is required to address students' comfort in working across cultural differences. The study recommends further refinement of active learning strategies to fully integrate tolerance into students' daily interactions.